Note on a thin-shell wormhole in extremal Reissner Nordstrom geometry - Mazharimousavi, S. Habib; Halilsoy, M. (World Scientific Publ Co Pte Ltd, 2018)
We show that the cold near horizon of the extremal Reissner-Nordstrom can be considered as the throat of a thin-shell wormhole with arbitrarily small exotic matter and positive angular pressure. Such a wormhole is physical and stable against radial perturbations provided an appropriate perfect fluid exists at the throat.
Keywords: Thin-shell wormhole; extremal Reissner-Nordstrom; stability